Age-related visual dynamics in HIV-infected adults with cognitive impairment. Issue 3 (May 2020) - Groff, Boman R.; Wiesman, Alex I.; Rezich, Michael T.; O'Neill, Jennifer; Robertson, Kevin R.; Fox, Howard S.; Swindells, Susan; Wilson, Tony W.
Abstract : Objective: To investigate whether aging differentially affects neural activity serving visuospatial processing in a large functional neuroimaging study of HIV-infected participants and to determine whether such aging effects are attributable to differences in the duration of HIV infection. Methods: A total of 170 participants, including 93 uninfected controls and 77 HIV-infected participants, underwent neuropsychological assessment followed by neuroimaging with magnetoencephalography (MEG). Time-frequency analysis of the MEG data followed by advanced image reconstruction of neural oscillatory activity and whole-brain statistical analyses were used to examine interactions between age, HIV infection, and cognitive status. Post hoc testing for a mediation effect of HIV infection duration on the relationship between age and neural activity was performed using a quasi-Bayesian approximation for significance testing. Results: Cognitively impaired HIV-infected participants were distinguished from unimpaired HIV-infected and control participants by their unique association between age and gamma oscillations in the parieto-occipital cortex. This relationship between age and gamma was fully mediated by the duration of HIV infection in cognitively impaired participants. Impaired HIV-infected participants were also distinguished by their atypical relationship between alpha oscillations and age in the superior parietal cortex. Conclusions: Impaired HIV-infected participants exhibited markedly different relationships between age and neural responses in the parieto-occipital cortices relative to their peers. This suggests a differential effect of chronological aging on the neural bases of visuospatial processing in a cognitively impaired subset of HIV-infected adults. Some of these relationships were fully accounted for by differences in HIV infection duration, whereas others were more readily associated with aging.